Meta-Analisis Pengaruh Bahan Ajar IPA Terpadu Bermuatan Literasi untuk Meningkatkan Pengetahuan Peserta Didik - Putri, Nurul Hasanah Daniyah; Agustina, Nelmi (Jurnal Penelitian Pembelajaran Fisika, 2021)
The aims of this study was analyze the effect of integrated science teaching materials with literacy to increase students' knowledge. This research method is a meta-analysis with a sample of 25 national and international educational journals. This article will reveal why it is important to develop teaching materials with literacy in view of educational studies. Things that need to be considered are the abstract, content, and conclusions of each journal. A meta-analysis study examines the effect of integrated science teaching materials with literacy based on education level, teaching material, and literacy content, research findings show that integrated science teaching materials filled with literacy is effective in improving student learning outcomes. Based on the type of integrated science teaching materials, worksheets with literacy have a high effectiveness value in improving student learning outcomes. The effect of integrated science teaching materials with literacy is effectively used to improve student learning outcomes when viewed from the literacy aspect. The effect of integrated science teaching materials with literacy content to improve students' understanding of using network structures and functions more effectively. Based on the level of education, the effect of integrated science teaching materials with literacy is more effectively used in class VIII to improve students' understanding.